Power Quality with MPPT Controller and Irradiance Uncertainty for Grid-Connected Photovoltaic Energy System - Acero J.F.C. (2020)
As a result, various phenomena that affect the quality of energy occur, identifying the inverter and converter as the equipment responsible for generating these phenomena. The methodology is based on the dependence of the total harmonic distortion on the current, solar irradiation, inverter output current, RMS voltage for the grid connection point, and active and non-active power registers. It was verified that the results obtained met the criteria established with the energy quality standards for connection to the grid, related to the work of the MPPT converter for each photovoltaic module and the uncertainty of the irradiance. The values of PF varied a lot during the day, reaching desired levels when the injected power approached the inverter rated power. Therefore, low levels of PF can be reduced by increasing the number of modules photovoltaic, since the inverter used is oversized. © 2020 IEEE.